The 4Fs of cotton: genome editing of cotton for fiber, food, feed, and fuel to achieve zero hunger - Saleem, Muhammad Sulyman; Khan, Sultan Habibullah; Ahmad, Aftab; Rana, Iqrar Ahmad; Naveed, Zunaira Afzal; Khan, Azeem Iqbal (Frontiers in Genome Editing, 2024)
Cotton is globally known for its high-priority cellulose-rich natural fiber. In addition to providing fiber for the textile industry, it is an important source material for edible oil, livestock feed, and fuel products. Global warming and the growing population are the major challenges to the world's agriculture and the potential risks to food security.In this context, improving output traits in cotton is necessary to achieve sustainable cotton production. During the last few years, high throughput omics techniques have aided in identifying crucial genes associated with traits of cotton fiber, seed, and plant architecture which could be targeted with more precision and efficiency through the CIRPSR/Cas-mediated genome editing technique. The various CRISPR/Cas systems such as CRISPR/Cas9, CRISPR/nCas9, and CRISPR/Cas12a have been employed to edit cotton genes associated with a wide range of traits including fiber length, flowering, leaf colour, rooting, seed oil, plant architecture, gossypol content, somatic embryogenesis, and biotic and abiotic stresses tolerance, highlighting its effectiveness in editing the cotton genome. Thus, CRISPR/Cas-mediated genome editing has emerged as a technique of choice to tailor crop phenotypes for better yield potential and environmental resilience. The review covers a comprehensive analysis of cotton phenotypic traits and their improvement with the help of the latest genome editing tools to improve fiber, food, feed, and fuel-associated genes of cotton to ensure food security.